Concentration-dependent effects of immunomodulatory cocktails on the generation of leukemia-derived dendritic cells, DCleu mediated T-cell activation and on-target/off-tumor toxicity - Rejeski, Hazal Aslan; Hartz, Anne; Rackl, Elias; Li, Lin; Schwepcke, Christoph; Rejeski, Kai; Schmid, Christoph; Rank, Andreas; Schmohl, Jörg; Kraemer, Doris; Bojko, Peter; Schmetzer, Helga Maria (Frontiers in Immunology, 2025)
Acute myeloid leukemia (AML) remains a devastating diagnosis in clear need of therapeutic advances. Both targeted dendritic cells (DC) and particularly leukemia-derived dendritic cells (DCleu) can exert potent anti-leukemic activity. By converting AML blasts into immune activating and leukemia-antigen presenting cells, DC/DCleu-generating protocols can induce immune responses against AML blasts. Such protocols combine approved response modifiers (i.e., GM-CSF and PGE1/OK-432/PGE2) that synergistically improve the conversion of AML blasts into (mature) DC/DCleu. To guide potential clinical application of these response modifiers, we analyzed three different DC-generating protocols that combine a constant GM-CSF dose with varying concentrations of PGE1 (Kit-M), OK-432 (Kit-I), and PGE2 (Kit-K). Here, we specifically aimed to assess how different response modifier concentrations impact DC/DCleu generation, immune cell activation and leukemic blast lysis. We found that all immunomodulatory kits were effective in generating mature and leukemia-derived DCs from healthy and leukemic whole blood. For Kit-M, we noted optimal generation of DC-subsets at intermediary concentration ranges of PGE1 (0.25-4.0 µg/mL), which facilitated upregulation of activated and memory T-cells upon mixed lymphocyte culture, and efficient anti-leukemic activity in cytotoxicity assays. For Kit-I, we observed DC/DCleu generation and enhanced T- and immune cell activation across a broader range of OK-432 concentrations (5-40 µg/mL), which also facilitated improved leukemic blast killing. In conclusion, our results highlight that Kit-mediated DC/DCleu generation, immune cell activation and blast lysis are dependent on the concentration of response modifiers, which will guide future clinical development. Overall, DCleu-based immunotherapy represents a promising treatment strategy for AML patients.